1985
DOI: 10.2307/2273980
|View full text |Cite
|
Sign up to set email alerts
|

The completeness of a predicate-functor logic

Abstract: Predicate-functor logic, as founded by W. V. Quine ([1960], [1971], [1976], [1981]), is first-order predicate logic without individual variables. Instead, adverbs or predicate functors make explicit the permutations and replications of argument-places familiarly indicated by shifting variables about. For the history of this approach, see Quine [1971, 309ff.]. With the evaporation of variables, individual constants naturally assimilate to singleton predicates or adverbs, leaving no logical subjects whatever of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…However, it was shown that on the level of sentences, the expressive power of the guarded relational algebra coincides with the guarded fragment. 3 We now provide a similar result in our setting, showing that GRA(e, p, s, \, ∩, ∃) is sententially equiexpressive with GF. We start by defining that a term guard of a term T of arity at least one is a term S with the following properties.…”
Section: A Algebra For the Guarded Fragmentsupporting
confidence: 65%
See 1 more Smart Citation
“…However, it was shown that on the level of sentences, the expressive power of the guarded relational algebra coincides with the guarded fragment. 3 We now provide a similar result in our setting, showing that GRA(e, p, s, \, ∩, ∃) is sententially equiexpressive with GF. We start by defining that a term guard of a term T of arity at least one is a term S with the following properties.…”
Section: A Algebra For the Guarded Fragmentsupporting
confidence: 65%
“…Predicate functor logic has been studied very little, and we are not aware of any work relating to complexity theory. The notable works within this framework include the complete axiomatizations given in [20] and [3]. Concerning further algebraic settings, Tarski's relation algebra (see [17]) is also related to our work, but focuses on binary relations.…”
Section: Introductionmentioning
confidence: 99%
“…For details, see Quine (1960) and Burgess (2005). Quine developed several different versions of PF-languages in his later work, and Bacon (1985) and Kuhn (1983) begin from a slightly different basic stock of functors for their axiomatizations and completeness proofs. For a presentation of natural deduction and examples of many proofs in PF, see Bacon (1985).…”
Section: Feature-placing Languagementioning
confidence: 99%
“…At least, they are unacceptable when given a flatfootedly realist construal. See Bacon (1985) and Kuhn (1983) for this presentation.…”
Section: Is Predicate Functorese a Notational Variant Of First-order mentioning
confidence: 99%
“…Correspondingly, the issue can be raised if some of these give us 'large' decidable fragments of predicate-logical inference in some practical sense (cf. Bacon 1985). REMARK.…”
Section: Natural Fragmentsmentioning
confidence: 99%